2020
DOI: 10.2139/ssrn.3564038
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Consequences of Serious Parental Health Shocks

Abstract: I show that serious, yet common, parental health shocks in childhood have immediate and lasting effects on mental health and human capital formation for children. Children who experience a parental health shock are more likely to have therapy and take anti-depressant medication following the shock. These children have lower test scores and school enrollment rates. The effect occurs immediately following the shock and persists at least into early adulthood. I find that the effect on test scores is no different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Furthermore, we consider more severe shocks than others in the literature who have found no effects once selection was taken care of (Le and Nguyen, 2017). Moreover, Kristiansen (2020) uses the same data as we do, and finds significant effects of parental health shocks on children's educational performance and attainment.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, we consider more severe shocks than others in the literature who have found no effects once selection was taken care of (Le and Nguyen, 2017). Moreover, Kristiansen (2020) uses the same data as we do, and finds significant effects of parental health shocks on children's educational performance and attainment.…”
Section: Discussionmentioning
confidence: 82%
“…The existing literature that studies the effect of parental health on children focuses mostly on how childrens' health and educational outcomes are affected (see, for example, Currie and Moretti, 2007;Bhalotra and Rawlings, 2011;Kristiansen, 2020). Some research has shown associations between parental health and child educational outcomes in the US (Andrews and Logan, 2010, using the ECLS-K; or Johnson and Reynolds, 2013 using the NLSY), while many papers use data from developing countries (such as Senne, 2014;Dhanaraj, 2016;Alam, 2015) or transition countries (Bratti and Mendola, 2014).…”
Section: Existing Literaturementioning
confidence: 99%
“…The existing literature that studies the effect of parental health on children focuses mostly on how childrens' health and educational outcomes are affected (see, for example, Currie and Moretti, 2007;Bhalotra and Rawlings, 2011;Kristiansen, 2020). Some research has shown associations between parental health and child educational outcomes in the US (Andrews and Logan, 2010, using the ECLS-K; or Johnson and Reynolds, 2013 using the NLSY), while many papers use data from developing countries (such as Senne, 2014;Dhanaraj, 2016;Alam, 2015) or transition countries (Bratti and Mendola, 2014).…”
Section: Existing Literaturementioning
confidence: 99%